The Effect of Physical Activity Interventions on Executive Function in Overweight and Obese Adults: A Systematic Review - María Elena Chávez-Hernández; Lizbeth De La Torre; Luis Miguel Rodríguez-Serrano; Marina Wöbbeking-Sánchez (Biomedicines)
Background/objectives: Overweight and obesity are global public health problems associated with chronic disease and mental health. Physical activity (PA) is essential throughout a person’s life; an active lifestyle helps people to live healthier lives and improve their functional and mental abilities, such as executive function (EF). This systematic review aimed to analyze the evidence on the effects of PA on EF in overweight and/or obese adults (≥18 years old). Methods: Records from the PubMed, ScienceDirect, and JSTOR databases were searched and, following the PRISMA guidelines, seven studies were included in the present systematic review. Risk of bias was assessed using the National Institute of Health Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results from the studies included indicate that acute, short-term, and long-term PA interventions are an effective strategy to improve inhibitory control, working memory, and processing speed in overweight and obese adults. Furthermore, evidence indicates that EF can be effective as a measure to predict adherence to PA programs and weight loss. Conclusions: Exercise and physical activity interventions are a promising therapeutic strategy to promote weight loss and improve EF in adults with overweight and obesity. Additionally, EF may be further explored as a predictor of healthy aging due to the choices made throughout life and the long-term benefits that result.